Unusually severe phenotype of neonatal primary hyperparathyroidism due to a heterozygous inactivating mutation in the CASR gene - Obermannová, Barbora; Banghová, Karolína; Šumník, Zdeněk; Dvořáková, Hana; Betka, Jan; Fencl, Filip; Koloušková, Stanislava; Cinek, Ondřej; Lebl, Jan (European journal of pediatrics, 2009)
We present a male patient with neonatal severe primary hyperparathyroidism, whose manifestation was exceptionally serious for the heterozygous inactivating mutation he carried in the CASR gene. The patient presented soon after birth with respiratory distress requiring long-term mechanical ventilation, bone and chest deformities, feeding problems, and hypotonia. He had hypercalcaemia, hypophosphataemia, and hyperparathyroidism. There was no known history of calcium metabolism disorders in the family. As the impact on calcaemia of a rescue therapy with bisphosphonates was only transient, a subtotal and subsequently total parathyroidectomy were performed in the fourth month of life. Afterwards his clinical status improved and the fractures healed, but his neuropsychological development is delayed due to cerebral atrophy. Genetic analysis revealed a heterozygous missense CASR mutation R185Q, and an approximately equal expression of the mutated and wild-type RNA in the parathyroid tissue. The mother of the child was homozygous for the wild-type allele; the father is unknown. In conclusion, this patient demonstrates how serious neonatal hyperparathyroidism can be when caused by a heterozygous mutation. This may be attributable to a combination of dominant-negative action of the mutant allele with an intrauterine foetal hyperparathyroidism developed in the mother's normocalcaemic environment, further aggravated by a putative maternal vitamin D deficiency during pregnancy.
Keywords: Infant, Newborn; heterozygot; Prenatal Diagnosis; Humans; Female; fenotyp; novorozenec; Hyperparathyroidism; Hypercalcemia; Receptors, Calcium-Sensing; paratyreoidektomie; lidé; ženské pohlaví; hyperparatyreóza; stupeň závažnosti nemoci; těhotenství; Phenotype; hyperkalcemie; Point Mutation; bodová mutace; Vitamin D Deficiency; nedostatek vitaminu D; Parathyroidectomy; Severity of Illness Index; Heterozygote; dospělí; Pregnancy; Adult; prenatální diagnóza; receptory "calcium-sensing"